The invention of wings [large type] - Kidd, Sue Monk (Thorndike Press large print basic series., 2014)
"The story follows Hetty 'Handful' Grimke, a Charleston slave, and Sarah, the daughter of the wealthy Grimke family. The novel begins on Sarah's eleventh birthday, when she is given ownership over Handful, who is to be her handmaid. "The Invention of Wings" follows the next thirty-five years of their lives. Inspired in part by the historical figure of Sarah Grimke (a feminist, suffragist and, importantly, an abolitionist), Kidd allows herself to go beyond the record to flesh out the inner lives of all the characters, both real and imagined"--